Immobilization of FDH on carbon felt by affinity binding strategy for CO2 conversion - Diego Maureira; Sady Roberto Rodriguez; Oscar Romero; Marina Guillén; Gregorio Álvaro; Lorena Wilson; Carminna Ottone (Results in Engineering)
Enzymatic conversion is a promising option for utilizing CO2 as a renewable C1 source for high-value chemicals due to the high selectivity and specificity of enzymes, their environmental friendliness, and their ability to operate under mild conditions. The present study addresses CO2 conversion by developing a novel biocatalyst for formic acid production. Immobilization of formate dehydrogenase (FDH) from Candida boidinii onto carbon felt (CF) using an affinity binding approach is explored. Pre-treatment of CF with HNO3 increased nickel content with respect to the untreated and KOH treated CF samples, resulting in a biocatalyst with the highest specific activity. The selected biocatalyst achieved a promising formic acid yield of 78 % under pressurized CO2 conditions. Utilizing an 8-bar pressurized reactor led to a productivity of 0.56 mol L⁻¹ h⁻¹. The biocatalyst efficiently catalyzed formic acid synthesis over four consecutive reaction cycles, but its efficiency decreased with each cycle. This research demonstrates the feasibility of simple and efficient FDH immobilization on CF for CO2 conversion. The resulting biocatalyst shows potential for formic acid production, but further investigation is needed to enhance reusability for industrial applications.